Penurunan Burnout Perawat Melalui Implementasi Relaksasi Autogenik - Nur, Hirza Ainin; Pramudaningsih, Icca Narayani; Pujiati, Eny; Cahyanti, Luluk; Yuliana, Alvi Ratna; Ambarwati; Jamaludin; Fitriana, Vera (JURNAL KESEHATAN PRIMER, 2024)
Background: Burnout is prolonged stress that is often experienced by nurses due to work fatigue. Nurses who experience burnout can cause fatal problems such as the risk of suicide in nurses, as well as a decrease in the quality of service for patients. One action that can be used to reduce burnout symptoms is autogenic relaxation. Objective: This research aims to determine the effectiveness of autogenic relaxation measures on nurse burnout. Method: The research method used is pre-experimental design with one group pretest-posttest design. The total sample was 22 respondents. Autogenic relaxation was carried out once every day for 1 week in the morning with a duration of 20 minutes. Data collection used observation sheets, autogenic relaxation SOPs, the Maslach Burnout Inventory (MBI) instrument. Statistical analysis uses the Wilcoxon Rank Test. Results: This research shows that autogenic relaxation is effective in reducing nurse burnout with p-value of 0.000 for emotional exhaustion, 0.000 depersonalization, 0.000 personal accomplishment.